RANCANG BANGUN ABSENSI MAHASISWA AMIK IBRAHIMY BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL - Meli Okviani (Jurnal Ilmiah Informatika, 2020)
The attendance list in AMIK Ibrahimy still applies manual way. The problems faced in this case are students sometimes do not find the attendance list paper since it is gone and there sometimes appears deceitfulness since the students can easily change their absence status to presence. The researcher wants to make web-based attendance list to enable the staffs and the lecturers in identifying the students’ presence in the attendance list, recapitulating the monthly attendance as well as identifying which students are present or absent during the lecture. To solve the problems, it is then made web-based attendance list of AMIK Ibrahimy students that can enable the staffs and the lecturers in processing the attendance list, recapitulating the attendance list in order to avoid any deceitfulness of students. The researcher intentionally uses web that can be accessed through laptop or computer for processing the attendance list. The attendance list application that is designed aims at helping the AMIK Ibrahimy students attendance list that is web-based. Through this web-based attendance list, it is expected that it can be more accurate, faster, and easier in processing the information even with the huge number of students.